SEASONAL VARIATIONS ON SERUM GLUCOSE AND LIPID PROFILE IN A MALE POIKILOTHERM VERTEBRATE, UROMASTYX HARDWICKII - Qureshi, Ghazala; Shirwany, Tanvir (Journal of Ayub Medical College Abbottabad, 2012)
Background: Uromastyx hardwickii, a local lacertilian species, is widely distributed in the Indo-Pak subcontinent and inhabits mostly the arid regions of the country. This study was carried out to assess the seasonal variations on glucose, cholesterol and triacylglycerol (TAG) levels in a poikilotherm vertebrate species and to develop an experimental model for the study of lipid metabolism in higher vertebrates including mammals. Methods: This cross-sectional study was carried out on male Uromastyx hardwickii. Sixty animals were bled and sacrificed within 48 hrs of their arrival in the laboratory. Blood samples were collected by anterior abdominal venepuncture from conscious animals using a heparinised syringe. Results: Mean serum TAG levels were significantly higher in summer, while no significant changes were seen in cholesterol level during different parts of the year. Mean serum glucose levels were significantly higher in summer. Conclusion: Lipid metabolism in Uromastyx hardwickii undergoes significant seasonal alteration. There is significant (p<0.05) increase in serum triglycerides during summer. Similarly, serum glucose also exhibits seasonal variation. Keywords: Uromastyx hardwickii, animal model, lipid profile, seasonal, triglyceride